Pragmatic realization of probability category in the range of “reality / irreality” in science-fiction novels - Христич, Ніна Сергіївна (Київський національний університет імені Тараса Шевченка, 2020)
The article presents the results of the study of probability category in the popular science fiction novels “The Expanse” by James S. Corey and “Blindsight” by Peter Watts. According to the author, the pragmatic realization of probability category in the area “reality / unreality” is to analyze the pragmatic content of a particular communicative situation of interaction of communication participants. The analysis of the pragmatic content of the language units is focused on establishing those elements that carry information about the future. Pragmatic realization of probability category in the area “reality / unreality” occurs not only in a semantic-functional way of sentence construction, but also through modality. The research material showed that the semantic division of modality is determined by two criteria: quantitative and qualitative assessment of the speaker’s knowledge. Selected cases of modal probability are transmitted by units of different language levels: lexical, lexical-grammatical, lexical-syntactic and syntactic. The position of probability markers is significant to determine the degree of probability of information in the English-language utterance. The author believes that this problem requires a multifaceted study. There are still a number of issues that require more detailed study, namely, semantics of expressing degrees of probability, the plurality of means of expressing modal relations, and so on.

У статті викладено результати дослідження категорії вірогідності у популярних науково-фантастичних романах “Простір” Джеймса С. Корі та “Хибна сліпота” Пітера Уоттса. На думку автора, прагматична реалізація значень вірогідності у площині «реальність / ірреальність» полягає в аналізі прагматичного наповнення конкретної комунікативної ситуації взаємодії учасників спілкування. Аналіз прагматичного змісту мовних одиниць орієнтований на встановлення в них тих елементів, котрі несуть інформацію щодо майбутнього. Прагматична реалізація категорії вірогідності у площині «реальність / ірреальність» відбувається не лише семантико-функціональним способом побудови речення, а й за допомогою модальності. Матеріал дослідження засвідчив, що семантичне членування модальності визначається двома критеріями: кількісною і якісною оцінкою знань мовця. Дібрані випадки модальності вірогідності передаються одиницями різних мовних рівнів: лексичного, лексико-граматичного, лексико-синтаксичного і синтаксичного. Для визначення читачем ступеня вірогідності інформації в англомовному висловлюванні значущою є позиція маркерів вірогідності. Автор вважає, що вказана проблема потребує багатогранного дослідження. Залишається коло питань, що потребують більш детального вивчення, а саме: семантика вираження ступенів вірогідності, а також у різноманітті засобів вираження модальних відносин.
Прагматична реалізація категорії вірогідності у площині “реальність / ірреальність” у науково-фантастичних романах
Keywords: probability category; modality; pragmatics; reality; unreality; science fiction novel; категорія вірогідності; модальність; прагматика; реальність; ірреальність; науково-фантастичний роман